PENERAPAN DISIPLIN APARATUR SIPIL NEGARA DI BADAN KEPEGAWAIAN DIKLT DAERAH KABUPATEN SIAU TAGULANDANG BIARO - RADJA, GREACE OKTAFIANI; LENGKONG, FLORENCE DAICY; PALAR, NOVIE ANDERS (JURNAL ADMINISTRASI PUBLIK, 2017)
This study focuses attention on the Application of Civil State Apparatus Discipline in the Regional PersonnelTraining Board of Siau Tagulandang Biaro Regency. This study was conducted because the discipline of the state civilapparatus has not complied with the prevailing government regulation. This research is expected to be useful for theGovernment of Siau Tagulandang Biaro Regency, especially in the Office of the Regional Personnel Training Agency inan effort to apply the discipline. This research was conducted at the office of the Regional Human Resources TrainingBoard of Siau Tagulandang Biaro Regency. As the selected informant is the head of the agency, Head of the sub-section ofgeneral and staffing, Head of field of mutation and promotion information, Head of appraisal performance appraisal andawards development, Head of discipline sub-division and awards together with 4 persons as staff. This research is conductedby in-depth interview and by way of direct observation on the implementation of disciplinary application of State civilapparatus. The results of this study indicate that in applying the discipline of state civil apparatus is firm but there are stillemployees who ignore the rules of discipline in effect proved that disciplinary violations still occur. Disciplinary behavioursthat often occur in the Regional Human Resources Training Board of Siau Tagulandang Biaro Regency. The conclusionthat the researcher got in this research is the regulation that has been made concerning discipline of civil servant not yeteffective executed because weakness of supervision from leader, civil apparatus of State still not realize its obligation soviolating prohibition. The researcher's suggestion from this research is to be more assertive from the leadership of thediscipline in the implementation of the discipline, the leader is more direct with all employees, so that the employees canreally perform the task in accordance with their obligations and need to be conducted research to improve the effectivenessof the Application of Civil State Apparatus Discipline the imposition of strict discipline this affects the employee when theEmployee performs. Likewise with employees in the BKDD to more understand and obey government regulations.Keywords: Implementation, Discipline, State Civil Apparatus.